Potential for the blood-based biomarkers cytokeratin 19 fragment (CYFRA 21-1) and human epididymal protein 4 (HE4) to detect recurrence during monitoring after surgical resection of adenocarcinoma of the lung - Muley, Thomas; Warth, Arne; Schneider, Marc; Herth, Felix (Lung cancer, 2019)
Objectives - The biomarkers cytokeratin 19 fragment (CYFRA 21-1) and human epididymis protein 4 (HE4) are useful in the diagnosis, prognosis, and monitoring of non-small cell lung cancer (NSCLC), but their combination has not been investigated yet. The objective of this analysis was to evaluate the ability of CYFRA 21-1 and HE4 to predict recurrence as part of follow-up monitoring in patients with adenocarcinoma (ADC) of the lung. - Materials and methods - Serum samples were collected from patients with stage I-IIIA ADC preoperatively and during follow-up at 3, 6, 12, 18, and 24 months and then every 6-12 months up to 5 years post-R0 resection. Samples were analyzed for CYFRA 21-1 and HE4 via electrochemiluminescence immunoassay. All cases of disease recurrence were verified by imaging. The diagnostic performance of CYFRA 21-1, HE4, and their combination to predict recurrence was assessed by Receiver Operating Characteristic (ROC) and corresponding area under the curve (AUC). - Results - 115 patients with ADC were included (N = 612 biomarker measurements); median age was 63 years; most had stage I-II disease (n = 97; 84.3%). All patients underwent surgical resection; 44 patients (38%) also received adjuvant chemotherapy and 16 (14%) received radiation therapy. At the median timepoint for the last blood sample collection (37 months), 31 patients (27%) had experienced recurrence. Both CYFRA 21-1 and HE4 were able to detect recurrence (AUC and 95% confidence interval [CI]): 75.9% (66.0-85.8%) and 75.4% (65.9-84.8%), respectively, but this increased with the combination (78.8% [69.0-88.6%]). At a sensitivity of 80%, the respective specificities (95% CI) for CYFRA 21-1, HE4, and the combination were 57.1% (53.0-61.2%), 57.1% (53.0-61.2%), and 69.7% (65.8-73.4%). - Conclusion - Serial measurements of serum CYFRA 21-1 and HE4 levels could provide a valuable method for follow-up monitoring of patients with ADC to detect recurrence.
Gesehen am 29.01.2020